Household types as a tool to understand adaptive capacity: case studies from Cambodia, Lao PDR, Bangladesh and India. (19th October 2016) - Williams, Liana J.; Afroz, Sharmin; Brown, Peter R.; Chialue, Lytoua; Grünbühel, Clemens M.; Jakimow, Tanya; Khan, Iqbal; Minea, Mao; Reddy, V. Ratna; Sacklokham, Silinthone; Santoyo Rio, Emmanuel; Soeun, Mak; et al.
Abstract : Supporting smallholder households to adapt to climate variability is a high priority for development agencies and national governments. Efforts to support climate adaptation in developing countries occur within highly dynamic contexts. Macro-level changes in national and regional economies manifest in dynamic local conditions, such as migration, changing household labour dynamics, market access and land-use options. Research aimed at developing adaptation options is often focused on particular activities or industries and struggles to take into account the broader, interrelated suite of household livelihood activities or the non-climate stressors driving change and adaptation. This paper explores the use of household types to (a) understand the diversity of household circumstances and (b) place agricultural adaptation options within the broader context of household livelihoods. Results from application in four countries are discussed, which highlight the utility of the method and identify broader level trends and drivers that are common challenges (experienced differently) across multiple contexts.